Odpowiedzi

Najlepsza Odpowiedź!
2010-01-04T21:53:22+01:00
A) (x+7)(2x-1)=2x²-x+14x-7=2x²+13x-7

b) (2a - 1)(a+4)=2a²+8a-a-4=2a²+7a-4

c) (4a-1)(2-3a)=8a-12a²-2+3a=-12a²+11a-2

d) (x+√5)(x-√5)=x²-5

e) (2y-√3)(y+1)=2y²+2y-y√3 -√3=2y²+y(2-√3) -√3

f) (a+ √2)(a-√3)=a²-a√3+a√2-√6=a²+a(√2 -√3)-√6

g) (2√2 + k)(√2-k)=4-2k√2+k√2-k²=-k²-k√2+4
2010-01-04T21:57:20+01:00
A) (x+7)(2x-1)= 2x[kwadrat]-x+14x-7=2x[kwadrat]+13x-7
b)(2a - 1)(a+4)=2a[kwadrat]+4a-a-4=2a[kwadrat]+3a-4
c) (4a-1)(2-3a)=8a-12a[kwadrat]-2+3a=11a-12a[kwadrat]-2
d)(x+√5)(x-√5)= x[kwadrat]-√5x+√5x-5=x[kwadrat]-5
e)(2y-√3)(y+1)=2y[kwadrat]+2y-√3y-√3
f) (a+ √2)(a-√3)=a[kwadrat]-√3a+√2a-√6
g) (2√2 + k)(√2-k)=4-2√2k+√2k-k[kwadrat]=-√2k-k[kwadrat]+4
powinno być ok ;)